Stewardship of Wild and Farmed Edible Insects as Food and Feed in Sub-Saharan Africa: A Perspective - Musundire, Robert; Ngonyama, Dianah; Chemura, Abel; Ngadze, Ruth Tambudzai; Jackson, Jose; Matanda, Margaret Jekanyika; Tarakini, Tawanda; Langton, Maud; Chiwona-Karltun, Linley (Frontiers in Veterinary Science, 2021)
Edible insects have gained popularity as alternative food resources in the face of climate change and increasing carbon and environmental footprints associated with conventional agricultural production. Among the positive attributes that make edible insects suitable as food and feed substrates include rapid reproduction, high energy conversion efficiency, wide distribution, diversity, reduced greenhouses gases and ammonia emissions, possibility to reduce waste and high nutritional composition. In Sub-Saharan Africa, considerable scientific data exist on use of insects as food and livestock feed. However, coherent policies regarding safety, sustainability, trade and regulation of insects as food and animal feed are lacking. The benefits associated with edible insects are likely to accrue in Sub-Saharan Africa through use of a combination of approaches such as ensured sustainable utilization of edible insects in the wild, preservation of traditional conservation, harvesting and consumption practices, development of captive mass production schemes and strengthening robust value chains to incentivise indigenous participants. These approaches can be collectively referred to as the steward and use of insects as food and animal feed. This paper is aimed at examining the policy frameworks that exist to support the use of edible insects as food and feed in the African continent. This investigation is a desktop exercise where national policies in selected African countries were assessed for their relevance to edible insects. Using a baseline of more than ten edible insect species consumed, ten countries in Sub-Saharan Africa were used to support our in-depth examination of the policy situation that may support good stewardship of edible insects as food and feed. Focus on how policies encompassing biodiversity, natural resources, culture, education, research, technology development, trade, health and nutrition and how that could be improved to support inclusivity of edible insects is discussed. We conclude by proposing a pathway that may accelerate recognition and valorisation of edible insects as important food and feed resources in Sub-Saharan Africa including improving policies to support good stewardship of these resources for sustainability.